Fibroblast-associated protein-α expression and BPV nucleic acid distribution in equine sarcoids. Issue 6 (November 2021) - Tura, Giorgia; Savini, Federica; Gallina, Laura; La Ragione, Roberto M.; Durham, Andy E.; Mazzeschi, Martina; Lauriola, Mattia; Avallone, Giancarlo; Sarli, Giuseppe; Brunetti, Barbara; Muscatello, Luisa V.; Girone, Cinzia; et al.
Sarcoids are the most common cutaneous tumor of equids and are caused by bovine papillomavirus (BPV). Different clinical subtypes of sarcoids are well characterized clinically but not histologically, and it is not known whether viral activity influences the clinical or histological appearance of the tumors. The aim of this study was to verify whether the development of different clinical types of sarcoids or the presence of certain histological features were associated with BPV distribution within the tumor. The presence of BPV was assessed by polymerase chain reaction (PCR) and visualized in histological sections by chromogenic in situ hybridization (CISH) in 74 equine sarcoids. Furthermore, to better characterize the molecular features of neoplastic cells, immunohistochemistry for S100, smooth muscle actin-α (αSMA), and fibroblast-associated protein-α (FAPα) was performed. The presence of BPV was confirmed in all tissues examined by either or both PCR and CISH (72/74, 97% each). Of 70/74 CISH-positive cases, signal distribution appeared as either diffuse (61/70, 87%) or subepithelial (9/70, 13%); the latter was more frequently observed in the verrucous subtype. However, no statistically significant association was found between clinical subtypes and specific histological features or hybridization pattern. Moreover, CISH signal for BPV was not detected in the epidermis overlying sarcoids nor in the tissue surrounding the neoplasms. By immunohistochemistry, αSMA confirmed the myofibroblastic differentiation of neoplastic cells in 28/74 (38%) sarcoids. Using tissue microarrays, FAPα labelling was observed in neoplastic fibroblasts of all sarcoids, suggesting this marker as a potential candidate for the immunohistochemical diagnosis of sarcoids.